Behavioral effects of a four-wing attractor with circuit realization: a cryptographic perspective on immersion. (12th November 2020) - Khan, Najeeb Alam; Qureshi, Muhammad Ali; Hameed, Tooba; Akbar, Saeed; Ullah, Saif
Abstract: In this paper, we propose an innovative chaotic system, combining fractional derivative and sine-hyperbolic nonlinearity with circuit execution. The study of this system is conducted via an analog circuit simulator, using two anti-parallel semiconductor diodes to provide hyperbolic sine nonlinearity, and to function as operational amplifiers. The multi-stability of the system is also enhanced with the help of multi-equilibrium points for distinct real orders of system. The system explores the generation of a four-wing attractor in different phases, both numerically and electronically. By changing the input parameters of the system, different graphs are generated for current flow in state, phase, and space, to confirm the precision of the fractional order derivatives. A reasonable simulation shows that the deliberate circuit provides effective chaos in terms of speed and accuracy, which is comensurate with the numerical simulation. This nonlinear chaotic behavior is utilized to encrypt sound (.wav), images (.jpg), and animated (.gif) data which are a major requirement for the security of communication systems. The proposed circuit performs chaos and cryptographic tasks with high-effective analog computation, and constitutes a novel approach to this area of research.